2019
DOI: 10.1007/s12223-019-00686-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of N and S poles of static magnetic field (SMF) on Candida albicans hyphal formation and antifungal activity of amphotericin B

Abstract: Due to the increasing number of Candida albicans’ infections and the resistance of this pathogenic fungus to drugs, new therapeutic strategies are sought. One of such strategies may be the use of static magnetic field (SMF). C. albicans cultures were subjected to static magnetic field of the induction 0.5 T in the presence of fluconazole and amphotericin B. We identified a reduction of C. albicans hyphal length. Also, a statistically significant additional effect on the viability of C. albicans was revealed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…Moreover, these results were in accordance with the recent studies of Novickij et al and Sztafrowski et al that showed the inhibitory effects of pulsed electric fields on the viability and hyphal length of C. albicans [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these results were in accordance with the recent studies of Novickij et al and Sztafrowski et al that showed the inhibitory effects of pulsed electric fields on the viability and hyphal length of C. albicans [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained in this study are in accordance with Sztafrowski et al's, showing that treating C. albicans with static magnetic fields (SEF) caused a significant reduction in tail-length of the germinated cells [36].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, there is a report of a slight decrease in viability of C . albicans CAF2-1 after 24h exposure (28°C) to SMF in comparison to the control conditions, where the average viability decreased by only 2.2% (N pole) to 3.4% (S pole) [ 17 ]. In turn, an application of a millisecond magnetic field (PEMF) resulted in a loss of pathogenic C .…”
Section: Discussionmentioning
confidence: 99%
“…albicans . Cells grown in a magnetic field showed a reduced growth intensity and increased sensitivity to the FLC and AMB [ 17 ]. As there are limited data on the effects of AMF on microorganisms, especially pathogenic yeast-like fungi, the purpose of this study was to indicate if AMF influences the overall survival and permeability of C .…”
Section: Introductionmentioning
confidence: 99%